Enhancing Cross-Border Cooperation (CBC) Between Poland and Czechia Through Euroregions: Opportunities and Challenges - Łukaniszyn-Domaszewska, Katarzyna; Śmietański, Roman (Publishing House of Wroclaw University of Economics and Business, 2024)
Cross-border cooperation is a critical aspect of regional development and integration within the European Union. In the case of Poland and Czechia, this cooperation is facilitated through Euroregions, transnational partnerships formed by border regions of different countries. The border between Czechia and Poland spans almost 800 km. Since 1991, six Euroregions and two European Groupings of Territorial Cooperation (EGTC) have been established, facilitating cross-border cooperation (CBC) along the entire length of the border. This institutionalisation of cross-border cooperation probably contributed to achieving and sustaining a high level of mutual Czech-Polish relations. This paper explores the opportunities and challenges of cross-border cooperation between Poland and Czechia within the framework of Euroregions, focusing on key initiatives, best practices, and areas for improvement.
Łukaniszyn-Domaszewska, K. & Śmietański, R. (2024). Enhancing Cross-Border Cooperation (CBC) Between Poland and Czechia Through Euroregions: Opportunities and Challenges. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 195-206). Publishing House of Wroclaw University of Economics and Business.
Keywords: cross-border cooperation; Euroregions; Polish-Czech relations; sustainable development